Cleaner production of biodiesel from novel non-edible seed oil (Carthamus lanatus L.) via highly reactive and recyclable green nano CoWO3@rGO composite in context of green energy adaptation. (15th January 2023) - Munir, Mamoona; Saeed, Muhammad; Ahmad, Mushtaq; Waseem, Amir; Alsaady, Mustafa; Asif, Saira; Ahmed, Anas; Shariq Khan, Mohd; Bokhari, Awais; Mubashir, Muhammad; Fatt Chuah, Lai; Loke Show, Pau
Graphical abstract: Highlights: Carthamus lanatus L. seed oil used for biodiesel production by using CoWO3@rGO. CoWO3@rGO is a novel, green and recyclable catalyst. The properties of the produced fuels met EN 14, 214 and ASTM D 6751. The optimal Carthamus lanatus L. biodiesel yield was predicted using RSM. The green nanocomposite can be reused seven times without losing reactivity. Abstract: Sustainable and cheaper intercession coupled with green technologies could be the feasible and finest approach for addressing the solicitous snags like energy crises, greenhouse gas emissions and fossil fuel depletions globally. Biodiesel appeared as a feasible substitute to achieve net zero emissions globally. Biodiesel produced from waste, toxic and non-edible oil seeds is clean, cheaper and capable for producing greener energy which ultimately contributed positively in boosting bio-economy (close circular economy). In the present study, the potential of Carthamus lanatus L. seed oil (CSO) as novel, non-edible and waste feedstock was investigated for producing biodiesel using cobalt tungstate loaded reduced graphene oxide (CoWO3 @rGO) as novel, green and recyclable catalysts. The catalyst (CoWO3 @rGO) was synthesized via Hummers method followed by characterizations by X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR) and energy dispersive X-ray analysis (EDX). Optimize biodiesel yield (99.7 wt%) was achieved with optimum reaction conditions of 0.8 wt% catalyst, oil to methanol molar ratio of 1:12 and temperature 65 °C for 2 h reaction time. The optimized Carthamus lanatus L. biodiesel (CBD) yield was also predicted by drawing 3D surface plots with response surface methodology (Box-Behnken design). The synthesized CBD was also characterized using latest techniques of nuclear magnetic resonance (NMR) ( 1 H and 13 C), Gas Chromatography/Mass spectroscopy (GC–MS) and FT-IR. The green nanocomposite exhibits excellent reusability of seven times without significant drop in its reactivity during transesterification process. Fuel properties of fatty acid methyl ester complied with biodiesel international standards EN 14214, China GB/T 20828–2007 and ASTM D 6751. Ultimately, biodiesel produced from wild, uncultivated and non-edible CSO can be commendably used to engender and adopt a greener and sustainable energy approach. The acceptance and adoption of the green energy approach could bring positive outcomes in the environment which ultimately create healthier societal and economic development.